Machine Learning for Hospital Readmission Risk Prediction: A Digital Health Imperative - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Machine Learning for Hospital Readmission Risk Prediction: A Digital Health Imperative Hospital readmissions—a patient returning to the hospital shortly...
Keywords: Digital Health; Diagnostics; Healthcare Innovation; Patient Care; Machine Learning